Copper interconnections and antennas fabricated by hot-pressing printed copper formate. (28th September 2017) - Rosen, Yitzchak S; Lidor, Yuval; Balter, Revital; Szeskin, Adi; Awadallah, Asad; Shacham-Diamand, Yosi; Magdassi, Shlomo
Abstract: We present a novel process to fabricate conductive patterns by a new copper precursor ink. In this method, an ink with copper formate, a self-reducible copper precursor, is printed, and subsequently heated under high pressure in a hot-press, which is commonly used in the printed circuit board industry. The heating leads to decomposition of the precursor, and results in copper patterns with good electrical conductivity. The application of pressure enables the formation of a dense copper film. 5–15 μ m thick copper patterns were obtained on FR4 sheets with an equivalent specific resistivity as low as 5.3 ± 0.3 μ Ω cm, which is about three times the copper bulk resistivity. Unlike most methods for copper precursor inks, this ink and process do not require an inert environment, and can be performed with instrumentation already used in the industry. Finally, we demonstrate the applicability of this method by printing functional radio frequency components; i.e. antennas for near field communication and Wi-Fi.